263 Use of an Air Purifier in the Bedroom Improves Objective and Perceived Sleep. (3rd May 2021) - Rus, Holly; Danoff-Burg, Sharon; Weaver, Morgan; Rodriguez, Rodolfo; Raymann, Roy
Abstract: Introduction: This study examined if an air purifier in the bedroom would improve sleep on a broad sample of healthy people (non-smokers without allergies) with sub-optimal sleep living in urban and suburban areas. This way of testing has the advantage of providing insight into the effectiveness of a product under real-life conditions, yielding more ecologically valid results. Methods: 36 adults whose objective data indicated suboptimal sleep participated in an 8-week field study. A within subjects, pre-post intervention design was implemented, comparing 4 weeks of nightly product use to 4 weeks without using the product. Intervention consisted of the use of an Alen BreatheSmart 45i air purifier in the bedroom for 24 hours a day during the duration of the intervention period. Sleep was measured objectively with SleepScore Max every night and by self-report. Multilevel regression and paired t-tests were used to test for statistical significance. Results: Across all participants there were 1591 nights of tracked sleep. Participants (55% male, age 25-74, avg. 44) showed improvement in both objective and perceived sleep during the intervention. While using the air purifier, there was a small but significant improvement in objective sleep quality (p<.05). In the subgroup of participants who had the poorest objective sleep at baseline (n=16), there were significant improvements while using the air purifier, reflecting improved sleep continuity after falling asleep: fewer awakenings during the night, decreased time awake during the night, increased sleep efficiency, and increased sleep maintenance (all ps<.05). Self-report data showed that, when using the air purifier, participants felt they fell asleep faster, woke up fewer times, spent less time awake at night, and were better able to sleep through the night. In the morning, they were more likely to feel well-rested. They also felt satisfied with their sleep more often and had better sleep quality (all ps<.05). Conclusion: Using the air purifier in the bedroom can improve sleep. Objectively measured sleep improvement supported self-reported sleep improvements, especially in the subset of participants who showed compromised sleep at baseline. Support (if any): Alen Corporation